2017
DOI: 10.29252/cmm.3.4.26
|View full text |Cite
|
Sign up to set email alerts
|

Mycological Aspects of Onychomycosis in Khuzestan Province, Iran, a New Scenario as Shift from Dermatophytes towards Yeasts

Abstract: Background and Purpose:Onychomycosis is fungal infection of the nails with an overall increasing incidence, worldwide. The epidemiological aspects of onychomycosis in Khuzestan, Iran, have not been established. In this study, we aimed to evaluate the clinical and mycological status of fungal nail infection in Khuzestan Province, Iran.Materials and Methods:The study population included 433 patients (143 males vs. 290 females). Nail samples underwent primary direct microscopy and culture. The isolated yeasts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
2
12
2
Order By: Relevance
“…Our data are in contrast with current available literature on the global epidemiology of onychomycosis, but they trace an epidemiological shift already reported in Iran, Brazil, India and Saudi Arabia . In fact, as reported, respectively, for the countries mentioned before, yeasts were found to be the causative agents of onychomycosis in the following: 59.7% in Iran, in Brazil, in 47.86% India and 46.8% in Saudi Arabia …”
Section: Discussioncontrasting
confidence: 99%
“…Our data are in contrast with current available literature on the global epidemiology of onychomycosis, but they trace an epidemiological shift already reported in Iran, Brazil, India and Saudi Arabia . In fact, as reported, respectively, for the countries mentioned before, yeasts were found to be the causative agents of onychomycosis in the following: 59.7% in Iran, in Brazil, in 47.86% India and 46.8% in Saudi Arabia …”
Section: Discussioncontrasting
confidence: 99%
“…in 50% of the nail samples, dermatophytes in 21% and ND moulds in 11% 2 . Similar fungal epidemiologies of onychomycoses were observed in surveys conducted in countries of the Middle East, Asia and South America 14‐17 . In a review on the worldwide prevalence of onychomycosis, Gupta et al 6 identified ND moulds as causative pathogens in roughly half of the onychomycosis cases for some regions.…”
Section: Resultsmentioning
confidence: 59%
“…In a review on the worldwide prevalence of onychomycosis, Gupta et al 6 identified ND moulds as causative pathogens in roughly half of the onychomycosis cases for some regions. These observations may in fact indicate an epidemiological trend towards an increased involvement of non‐dermatophyte pathogens in onychomycosis 14 …”
Section: Resultsmentioning
confidence: 94%
“…No speciesdependent difference was observed in hypoxic cultures, leading to the assumption that all species are similarly able to cause invasive disease, as also reflected by clinical data. Only A. floccosus has so far never been described to cause invasive disease [21,37].…”
Section: Discussionmentioning
confidence: 99%